In silico characterizations of degradative enzyme from landfill leachate metagenome for potential polychlorinated biphenyl (PCB) bioremediation - Drahaman, Siti Marhamah; Nordin, Noor Faizul Hadry; Mohd Salleh, Hamzah; Ahmad Tajuddin, Husna (IIUM Press, 2025)
The characterization of enzyme structure and function was essential for understanding biochemical pathways and developing effective biotechnological applications, particularly in environmental bioremediation. Traditional experimental methods for protein analysis were often labor-intensive and limited by the inability to culture certain microorganisms. In this study, an in silico approach was employed to predict the structure and function of a putative degradative enzyme identified from metagenomic analysis of landfill leachate. Using a combination of bioinformatics tools, including sequence alignment, domain annotation, secondary structure prediction and three-dimensional (3D) structural modeling, the target enzyme was analyzed for its catalytic potential and stability. Conserved motifs and active sites were identified, suggesting its involvement in the degradation of xenobiotic compounds such as polychlorinated biphenyls (PCBs). The 3D structure model revealed a typical fold associated with oxygenase or dehydrogenase activities, with predicted metal-binding sites critical for catalyses. These findings demonstrate the power of computational methods to accelerate the discovery and characterization of novel enzymes, especially from unculturable microbial communities. This approach provides a valuable foundation for future functional validation, protein engineering and the development of environmentally sustainable biocatalysts